Le bio-bibliografie immaginarie di Bolano e le biografie infedeli di Orecchio come approcci letterari alle verita della storia, della vita - Farinelli, Patrizia (Ars et humanitas, 2017)
There is one type of biography that maintains an ambiguity with regard to what is true and what is not, being based solely on fiction or a mixture of documented and invented information. Such a form has been used in literature for more than a century, but became especially popular with the rise of postmodernism. With its help it is easier to notice the problematic traits of a traditionally impersonal biography and at the same time reflect on the identity of literary discourse. We are thus going to examine two works, published in the last two decades, which can be considered as examples of such literary production. The first is Roberto Bolano's La literatura nazi en América (Nazi Literature in the Americas), published in 1996, and based on imaginary facts set in a historically realistic context. The second one, published in 2012, is Davide Orecchio's Citta distrutte: sei biografie infedeli, which depicts with fictional biographies the lives of real people and actual historical events (among others, fascism in Italy and dictatorship in Argentina). The analysis reveals some specific strategies and possible aims and, in particular, points out that behind various ingenious narrative choices (capable of misleading the reader with their parody of traditional biographical discourse) there is a radical reference to historical consciousness.
Keywords: biofikcija; Bolano, Roberto; čas; italijanska književnost; latinskoameriške književnosti; namišljeni citati; Orecchio, David; parodija; polfiktivna biografija